ISLAM WARNA-WARNI MENAFSIR ULANG KONSEP UMMATAN WASATHAN - Muhammad Abraar (NIHAYAH: Journal of Islamic Studies, 2025)
This article reinterprets the concept of ummatan wasathan, which is often understood within a normative framework of religious moderation. Employing a qualitative approach that integrates classical Islamic text analysis, ethnographic observation, and contemporary case studies, this study examines the multiple meanings of wasathiyah in Indonesia’s multicultural Muslim society. The findings reveal three dominant interpretations of wasathiyah: normative-textual, contextual-progressive, and pragmatic-political. These variants compete in shaping public Islamic discourse, often resulting in conflict and limited inclusivity. Although presented as a middle path, wasathiyah discourse is frequently used as a tool of power to legitimize authority and marginalize dissenting voices. The article highlights the necessity of reimagining a more inclusive Islam by expanding interpretive space around wasathiyah, making it more reflective of contemporary Muslim social realities. By recognizing pluralism as an inevitable fact, the study recommends developing a more dialogical religious education model and a flexible Islamic framework that embraces diversity. This research contributes to the Islamic discourse by offering a new perspective on moderation, viewing it not as a fixed ideology but as a dynamic, plural, and context-sensitive process.